2015
DOI: 10.3109/00365521.2015.1079646
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant versus sequential therapy for the treatment ofHelicobacter pyloriinfection: a Greek randomized prospective study

Abstract: Concomitant therapy led to statistically significant higher eradication rates over sequential therapy. Both therapies showed excellent compliance and an acceptable safety profile. The 10-day quadruple concomitant scheme should be the adopted for first-line H. pylori eradication in Greece.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 33 publications
0
27
2
Order By: Relevance
“…These results were even slightly higher than expected according to most recent studies that reported eradication rates ranging from 83% to 95% with CQT [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] and from 80% to 95% with BQT. Eradication rate obtained by both strategies was similar and clearly above the recommended 90% eradication rate (CQT 98.0% and BQT 94.4% at ITT analysis).…”
Section: The Addition Of Certain Probiotics (Different Lactobacillus Andcontrasting
confidence: 58%
See 1 more Smart Citation
“…These results were even slightly higher than expected according to most recent studies that reported eradication rates ranging from 83% to 95% with CQT [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] and from 80% to 95% with BQT. Eradication rate obtained by both strategies was similar and clearly above the recommended 90% eradication rate (CQT 98.0% and BQT 94.4% at ITT analysis).…”
Section: The Addition Of Certain Probiotics (Different Lactobacillus Andcontrasting
confidence: 58%
“…Eradication rate obtained by both strategies was similar and clearly above the recommended 90% eradication rate (CQT 98.0% and BQT 94.4% at ITT analysis). These results were even slightly higher than expected according to most recent studies that reported eradication rates ranging from 83% to 95% with CQT [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] and from 80% to 95% with BQT. 25,[30][31][32][33][34][35][36][37][38][39] Since eradication rates of different therapies depend on the H pylori resistance pattern to antibiotics, our results are region specific and only applicable to areas with similar resistance rates to main antibiotics.…”
Section: The Addition Of Certain Probiotics (Different Lactobacillus Andcontrasting
confidence: 58%
“…Recent studies of the comparison of concomitant therapy with sequential therapy in the same period reported the superior efficacy of concomitant therapy . The most important reason for the superior efficacy of concomitant therapy over sequential therapy was that the sequential therapy was less effective in antibiotic‐resistant strains.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies compared ST to concomitant (four drugs: amoxicillin, clarithromycin, metronidazole, and PPI) therapy. A randomised study from Greece showed superior eradication for 10 days of the concomitant regime compared to 10‐day ST (84.6% vs 70.9%) . Another study from Korea looked at a 7‐day concomitant regimen and also found superior rates of eradication compared to the ST (90.3% vs 85.5%) .…”
Section: Sequential Therapymentioning
confidence: 99%
“…A randomised study from Greece showed superior eradication for 10 days of the concomitant regime compared to 10-day ST (84.6% vs 70.9%). 33 Another study from Korea looked at a 7-day concomitant regimen and also found superior rates of eradication compared to the ST (90.3% vs 85.5%). 34 A meta-analysis of randomised studies showed concomitant therapy did not achieve higher eradication rates compared with the ST regimen with…”
Section: Sequential Therapymentioning
confidence: 99%